All the apostles of the Bible studies in the characters of the apostles, the men Jesus chose and the message they proclaimed. - Lockyer, Herbert, 1886- (Grand Rapids, MI Zondervan, 1972)
Includes bibliographical references and index.
Brethren writer.
Keywords: APOSTLES - THE TWELVE; APOSTLES - WIDER CIRCLE; TWELVE APOSTLES; Apostles -- biography